Strategi Pengembangan Usaha Mikro dan Kecil Sektor Wisata Bahari di Pulau Kecil (Studi Kasus Pulau Bunaken, Kota Manado, Sulawesi Utara) - Tria Friliyantin; Aida Vitayala S Hubeis; Aris Munandar (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
As a part of ecotourism, marine tourism activities depend on the attractiveness of the marine itself. This marine tourism becomes one of promising marine industry for year to year comes. The attractiveness of the marine tourism is diversely including marine traveling, marine observing and many activities right on the coast and ocean per day, such as fishing, diving, surfing, canoeing as well as traditional ceremony which takes place right on the ocean or beaches. Businesses categorized as small, middle to micro business become supporting business in developing marine ecotourism particularly in small island.  Some of these developing businesses which support the marine tourism activity are small bars and restaurants, souvenir shops, renting equipments for snorkling, diving, surfing, jet skying, game fishing and boating, renting small transportation such as bicycles, motorcycles, cars, and some other services including translaters, snack selling including coconut selling and other economic generating activities.  The aims to the study are (1) to identify any small business which support marine tourism in small island, (2) to analyze small business management related to marine tourisme which able to awaken local community to achieve better local incomes, and (3) to perform strategic development of the small business supporting marine tourism in small island which can be applied individually or group of people.  Purposive sampling method was applied to obtain respondents of small island population, by means the respondents are determined based on the qualification made for the study. Scenario analysis was performed in order to obtain the link story, scenaries were performed, they were pesimistic, semi pesimistic, semi optimistic, and optimistic.  The developing strategy for small business management which supporting marine tourism of small island then was analyzed by using internal and external factors which included social, economics, social facilities, environments and policies, presumably all of these factors would affect the development of the marine tourism industry from now untill the years come. Analytical Hierarchy Process (AHP) was used in order to obtain the accurate decision made for determining strategic alternative of developing small business related to marine tourism in small island.  The obtaining strategic alternatives were (a) the use of a small island as an object for small business in marine tourism, (b) awakening of local community related to many sectors of marine tourism, (c) mechanism improvement of the marine tourism management in small island, (d) development of marine tourism facilities in the small island, (e) improvement of human/local capacity and capability which supporting the business, and (f) improvement of policies maikin and agencies.       All of these strategic alternatives were applied in strategic analisys for developing of small business in marine tourism sector which suitable to be applied in others small islands. It was also expected that these analysis strategics were able to accomodate many other stakeholders with their wills to evoke local community capacity in which in return this would be able to stimulate sustainable and natural resources based economic growth locally and nationally